2017
DOI: 10.1097/mib.0000000000001181
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Balloon Dilation Size and Avoidance of Surgery in Stricturing Crohnʼs Disease

Abstract: BACKGROUND Endoscopic balloon dilation (EBD) is an effective method for treating stricture-related obstruction in Crohn’s disease (CD). We aimed to identify factors predictive of successful avoidance of surgery, including endoscopic features, in patients undergoing balloon dilation. METHODS We performed a retrospective review of patients with symptomatic CD-related intestinal strictures undergoing EBD. Clinical, medication use, laboratory, and dilation data, including the minimum and maximum balloon sizes us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…budesonide) and systemically active corticosteroids was mentioned in the majority of cited studies. 8,9,10,11,13,14,15,28,29,30 However, the impact of steroid use on efficacy and adverse events was not specified in those studies. IBD patients undergoing colonoscopy, especially EBD, exhibited a higher risk for procedure-associated perforation than non-IBD or non-intervention controls.…”
Section: Pre Procedural Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…budesonide) and systemically active corticosteroids was mentioned in the majority of cited studies. 8,9,10,11,13,14,15,28,29,30 However, the impact of steroid use on efficacy and adverse events was not specified in those studies. IBD patients undergoing colonoscopy, especially EBD, exhibited a higher risk for procedure-associated perforation than non-IBD or non-intervention controls.…”
Section: Pre Procedural Preparationmentioning
confidence: 99%
“…Concurrent or prior use of biological agents ranged from 5.6% to 86.3% patients. 8,9,10,11,14,15,21,22,26,28,29,30,47 No published data exist associating the efficacy or adverse events of EBD with concurrent biological agent use (Recommendation Table 3-1-9).…”
Section: Pre Procedural Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to EBD technique, the maximum balloon diameter recorded in the studies ranged from 15 to 25 mm, but an increased caliber of dilation neither resulted in increased rates of clinical efficacy nor reduced the need for redilation or surgery . In a recent retrospective review of patients with symptomatic CD‐related strictures undergoing EBD, Reutemann and colleagues found that although there was no difference in the risk of future surgery between maximum EBD sizes of 14 to 15 mm and 16 to 18 mm, those reaching 16 to 18 mm exhibited a longer interval between subsequent dilations (mean 240 ± 136.7 vs 456 ± 357.3 days, respectively, P = 0.023) . Moreover, dilating strictures up to 25 mm had a higher than average complication rates.…”
Section: Management Of Crohn's Disease Associated Stricturesmentioning
confidence: 99%